Evaluation and performance of gross pollutant traps (GPTs) for open channel flow - Romali, Noor Suraya (2008)
Nowadays, water has become a scarce resource due to the water contamination problem. Pollution carried by urban stormwater is considered as one of the significant contributor to the degradation of receiving waters. One way to minimize water pollution is by constructing Gross Pollutant Traps (GPTs) at the point source to treat polluted water prior to being discharged into the river. This study emphasizes on the utilization of GPTs in removing pollutants during dry and wet weather conditions especially during stormwater events in open channel system. The GPTs system is consist of rubbish trap, oil and grease trap, and biofilter which located at Block L50, UTM Skudai. The results indicated that the GPTs system is effective in improving water quality during storm event where the effluent of discharge water of the GPTs system are comply with parameter limit as stated in Standard A and Standard B of Environmental Quality Act (1974). First flush analysis shows that the concentration of pollutants in first flush runoff is found more polluted than the remainder while the values of EMC for TSS, COD, and BOD are higher compared to other pollutants. Despite of functioned for water quality control, the GPTs is also benefit for water quantity control where it provide detention time, storage, and decrease the peak flow of the water flowing through the system.